2020
DOI: 10.2147/cmar.s249041
|View full text |Cite
|
Sign up to set email alerts
|

<p>Advances in the Detection Technologies and Clinical Applications of Circulating Tumor DNA in Metastatic Breast Cancer</p>

Abstract: Breast cancer (BC) represents the most commonly diagnosed cancer among females worldwide. Although targeted therapy has greatly improved the efficacy of treating BC, a large proportion of BC patients eventually develop recurrence or metastasis. Traditional invasive tumor tissue biopsy is short of comprehensiveness in tumor assessment due to heterogeneity. Liquid biopsy, an attractive non-invasive approach mainly including circulating tumor cell and circulating tumor DNA (ctDNA), has been widely utilized in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 122 publications
0
18
0
Order By: Relevance
“…As shown in Table 1 , four studies (BOLERO-2, SoFEA, PALOMA-3, and FERGI) revealed a high prevalence of ESR1 mutations in second and higher treatment line, with a total mutation rate of 32% (684/2136), while one study (MONALEESA-2) evaluated the ESR1 mutations in first-line treatment and reported a low prevalence of ESR1 mutations (4%). Our previous work revealed an ESR1 mutation rate of 24.7% (169/685) in the HR+ MBC patients ( 19 ). And this proportion seemed to be higher (30%–40%) in ER+ HER2- MBC patients who had resistance to ET, especially to AIs ( 31 ).…”
Section: Overview Of Esr1 Mutations In Mbcmentioning
confidence: 94%
See 4 more Smart Citations
“…As shown in Table 1 , four studies (BOLERO-2, SoFEA, PALOMA-3, and FERGI) revealed a high prevalence of ESR1 mutations in second and higher treatment line, with a total mutation rate of 32% (684/2136), while one study (MONALEESA-2) evaluated the ESR1 mutations in first-line treatment and reported a low prevalence of ESR1 mutations (4%). Our previous work revealed an ESR1 mutation rate of 24.7% (169/685) in the HR+ MBC patients ( 19 ). And this proportion seemed to be higher (30%–40%) in ER+ HER2- MBC patients who had resistance to ET, especially to AIs ( 31 ).…”
Section: Overview Of Esr1 Mutations In Mbcmentioning
confidence: 94%
“…The most commonly detected ESR1 point mutations locate in codons 380, 537, and 538 within the LBD ( 19 , 26 ) ( Figure 1B ). Several large-scale clinical trials have investigated the prevalence of ctDNA ESR1 mutations in ER+ MBC patients ( 27 30 ).…”
Section: Overview Of Esr1 Mutations In Mbcmentioning
confidence: 99%
See 3 more Smart Citations